Особливості сувенірної продукції «кубік-конструктор» - Книшов, Д. (My University, 2020)
The article deals with souvenir products "Cube Designer", which allows the use of 12 images. They are hidden one after another. This souvenir product can be used for a personal gift or to attract future applicants
Keywords: сувенірна продукція; «кубік-конструктор»